2004
DOI: 10.1016/j.tecto.2003.11.007
|View full text |Cite
|
Sign up to set email alerts
|

About the lithospheric structure of central Tibet, based on seismic data from the INDEPTH III profile

Abstract: Signals from 11 shots and 8 earthquakes, and numerous teleseismic events were recorded along the 400-km seismic line INDEPTH III in central Tibet and interpreted together with previous seismic and tectonic data. The abnormal behavior of various mantle phases reveals a complex Moho-transition zone, especially in the northern part of the line, in the Changtang Block, where the lower crust and the mantle show unusually low velocities, a shingled appearance of P n and no low-velocity layer in the upper crust. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 60 publications
4
34
0
Order By: Relevance
“…The passage of lower crustal flow is probably located in the low velocity zone in lower crust . These results have the similar implications to those of many other geophysical measurements [29,44,45,48,49] carried out in the Tibetan Plateau. They constitute the deep environment of lower crustal flow existence.…”
Section: Discussionsupporting
confidence: 88%
“…The passage of lower crustal flow is probably located in the low velocity zone in lower crust . These results have the similar implications to those of many other geophysical measurements [29,44,45,48,49] carried out in the Tibetan Plateau. They constitute the deep environment of lower crustal flow existence.…”
Section: Discussionsupporting
confidence: 88%
“…These coincident south‐to‐north changes have been interpreted by a number of investigators to mark the northern limit of relatively old, cold Indian mantle lithosphere thrust beneath Tibet during Tertiary time (summarized by Owens and Zandt [1997]). There are also crustal differences on either side of the BNS, with seismically faster crust to the south compared to the north [ Mechie et al , 2004; Meissner et al , 2004]. …”
Section: Banggong‐nujiang Suture: Geological Settingmentioning
confidence: 99%
“…These first‐order features are evident in both RLM2DI and RRI final models, though their forms are different due to the different spatial smoothing approaches used in the two algorithms. This rapid change in resistivity occurs at the same location as a dramatic change of seismic polarization anisotropy (Figure 3), from <0.5 s to the south to >1.5 s to the north [ Huang et al , 2000], and a subvertical, low‐velocity anomaly to midcrustal (∼30 km) depths [ Haines et al , 2003; Mechie et al , 2004; Meissner et al , 2004]. …”
Section: Data Inversionmentioning
confidence: 99%
“…A high geothermal gradient can reduce shear-wave velocity and may cause partial melting in the crust. Many studies revealed that partial melting exists in the crust beneath the Tibetan plateau, for example, in the middle crust beneath southern Tibet (Nelson et al, 1996;Unsworth et al, 2005) and in the middle-lower crust and upper mantle beneath northern Tibet (Wei et al, 2001;Meissner et al, 2004). In the southeastern Tibetan plateau, a high large-scale Poisson's ratio (0.22-0.32) was observed, suggesting heterogeneity in crustal composition and the existence of partial melting (Xu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%